SIMULASI PERUBAHAN BEBAN PEMBANGKIT LISTRIK TENAGA UAP: STUDI KASUS DI GORONTALO UTARA - Nurdin Hasananto Teguh; Djarot Bangun Darmadi; Lilis Yuliati (Jurnal Rekayasa Mesin, 2022)
Conceptual and design studies on 25 MW Northen Gorontalo steam based power plant are carried out under the existing comissioning data at four different load. The urgency of this study is related with supporting the prevention of greenhouse gass  emission and completing indonesian power plant energy map. This observation conducted by simulating those condition in Gatecycle  software and analyzing the output parameter to determine the power plant performance specifically heat rate, heat transfer duty, efficiency, power generated and fuel consumption.The study outcomes shows that heat rate at 50% TMCR was increased as much as 50 kcal/kwh as the load ramped down indicating power plant requires more energy to generate similar amount of  power. While the fuel consumption, power, and efficiency proportionally werer increased as the power plant load ramping up. Comparing thirteen equipments heat transfer, condenser was conducting the highest heat transfer duty followed by boiler and first stage of superheater.